Ranking Techniques in Indonesian Language Instructional - Sinta Bella; Ike Nur Sapitri; Lia Nuraeni; Rika Amelia; Yayan Sudrajat (PT. Lancar Media Komunikasi, 2022)
The results of the assessment of a lesson will provide motivation for students to perform better, known as rankings or rankings. The higher the ranking, the better the learning achievement, the lower the ranking, the worse the learning achievement. This applies from elementary school, junior high school to high school. Each student will compete with each other to be the highest rank in his school. The purpose of writing this article is to find out the ranking of students, the purpose of ranking in the learning aspect, the use of ranking, and ranking techniques. Keywords: Student Rankings, Ranking Purposes, Ranking Uses, and Ranking Techniques